The Process of Comprehension from a Psycholinguistic Approach – Implications for Translation - Hatzidaki, Anna (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe present paper provides a psycholinguistic approach to the process of comprehension. Namely, how people represent and make use of the literal and figurative meaning of words and sentences, how they decode the communicative purpose of linguistic elements, and how memory is involved in this decoding. By explaining the findings of psycholinguistic studies on the mental processes that underlie the comprehension of language, we show (i) how closely related translatology and psycholinguistics can be, and (ii) suggest ways in which knowledge of the latter may be used to both enrich theories and practices of the former, and in the instruction of future translators.